Incidence and Severity of SARS-CoV-2 Infection in HIV-Infected Individuals During the First Year of the Pandemic. (15th April 2022) - Rial-Crestelo, David; Bisbal, Otilia; Font, Rebeca; De Lagarde, Maria; Pinto, Adriana; Arce-García, Octavio; Santacreu-Guerrero, Mireia; Bermejo-Plaza, Laura; Rubio, Rafael; Pulido, Federico
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: We aim to investigate the infection rate, the clinical characteristics and outcomes of COVID-19-disease in a cohort of people living with HIV in Madrid (Spain), during the first year of pandemics. Setting: Observational single-center study, in which we included all HIV-infected patients (aged ≥ 18 years) with laboratory-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection as of February 28, 2021, at the Hospital Universitario 12 de Octubre. Methods: Confirmed disease was defined as any patient with a positive antigen test, reverse transcriptase polymerase chain reaction, or serology for SARS-CoV-2. We compared the characteristics of patients with mild disease (asymptomatic included) with those with moderate or severe disease (requiring admission). Results: Of 2344 HIV-infected patients, 158 (82.9% male; median age, 46.5 years) were diagnosed with SARS-CoV-2 (infection rate, 6.74%; 95% confidence interval, 5.79 to 7.83). Thirty-nine individuals (24.7%) had moderate or severe disease, 43.7% had mild disease, and 31.6% were asymptomatic. Hypertension (23.4%) and obesity (15.8%) were the most prevalent comorbidities; 12.7% had at least 2 comorbidities. One hundred forty-five patients (97.3%) had RNA-HIV viral load of <50 copies per milliliter, and only 3 had CD4 cell count of <200 cells per cubic millimeter before infection. Of those admitted to hospital, 59% required oxygen support and 15.4%, invasive mechanical ventilation. Five patients died. None of the patient taking tenofovir-disoproxil-fumarate required admission. In the multivariate analysis, age remained as the only independent factor for moderate-severe disease (odds ratio, 1.09; 95% confidence interval 1.04 to 1.14; P < 0.001). Conclusions: People living with HIV are at risk of severe SARS-CoV-2 infection. Age was the only variable with an independent association with moderate-severe disease, after adjusting by comorbidities and other factors.